Hydration Sensing: A Wearable Hydration Sensor with Conformal Nanowire Electrodes (Adv. Healthcare Mater. 6/2017). Issue 6 (March 2017) - Yao, Shanshan; Myers, Amanda; Malhotra, Abhishek; Lin, Feiyan; Bozkurt, Alper; Muth, John F.; Zhu, Yong
Abstract : A wearable skin hydration sensor is developed by Y. Zhu, J. F. Muth, and co‐workers in article number 1601159. The sensor is made of silver nanowires inlaid in a silicone substrate, which renders the sensor flexible and stretchable. Integrated systems with multimodal sensing capability (e.g., hydration, strain/motion and electrophysiological sensing) are demonstrated in two form factors — wristband and chest patch. Image design by Shanshan Yao.